Food chemistry: The role of additives, preservatives and adulteration - Sen, Mousumi (Wiley, 2022)
The book also presents detailed information about the chemistry of each major class of food additive and their multiple functionalities. In addition, numerous recent findings are covered, along with an explanation of how their quality is ascertained and consumer safety ensured.